1989
DOI: 10.1016/0166-6851(89)90084-4
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerca volvulus heat shock protein 70 is a major immunogen in amicrofilaremic individuals from a filariasis-endemic area

Abstract: Infestation with organisms causing lymphatic filariasis (i.e. Wuchereria bancrofti and Brugia malayi) results in a variety of clinical presentations. It is possible that some of the variation is due to differences in host response to parasite. To determine whether individuals who live in an endemic area but differ in their clinical manifestations respond to different filarial antigens, we screened Onchocerca volvulus expression libraries with sera from a number of individuals belonging to different clinical gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 13 publications
0
22
1
Order By: Relevance
“…Not only are the HSPs of Plasmodium falciparum antigenic, but T-cells reactive to the P. falciparum HSP70-1 protein have been described (Behr et al 1992). HSPs from the helminths Schistosoma mansoni (Johnson et al 1989) and Onchocerca volvulus (Rothstein et al 1989) are antigenic. Antibodies and T-cells from patients with autoimmune diseases have recognized HSPs from several infectious agents, including Mycobacteria (Rambukkana et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Not only are the HSPs of Plasmodium falciparum antigenic, but T-cells reactive to the P. falciparum HSP70-1 protein have been described (Behr et al 1992). HSPs from the helminths Schistosoma mansoni (Johnson et al 1989) and Onchocerca volvulus (Rothstein et al 1989) are antigenic. Antibodies and T-cells from patients with autoimmune diseases have recognized HSPs from several infectious agents, including Mycobacteria (Rambukkana et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of Hsps: large Hsps such as Hsp60, Hsp70, and Hsp90, as well as small Hsps with molecular masses of 12–43 kDa [16], [17]. Several Hsps have been characterized in parasitic nematodes: Hsp20 in N. brasiliensis [18]; Hsp20 and Hsp70 in Haemonchus contortus [19], [20]; Hsp70 in Onchocerca volvulus and Parastrongyloides trichosuri [21], [22]; and Hsp12.6, Hsp18, and Hsp90 in Brugia spp. [23]–[25].…”
Section: Introductionmentioning
confidence: 99%
“…BCG is widely used as a vaccine against tuberculosis, and a large number of people are sensitized to mycobacteria or other parasites through natural contacts. Moreover, sensitization to HSPs has been reported to occur in individuals naturally exposed to a wide variety of infections, such as malaria (24), filariasis (34,37), schistosomiasis (27), American trypanosomiasis (12), leprosy (9,25), and candidiasis (17). It has also been reported that vaccination against pertussis using a whole-cell vaccine is capable of priming the immune system to respond to microbial HSPs (10).…”
Section: Discussionmentioning
confidence: 99%